The Analysis of Racism toward African-American as seen in Selected Phillis Wheatley’s Poems - Dyny Wahyu Seputri; Iffah Fikzia; Krisna Sujiwa (Universitas Gadjah Mada, 2022)
The issues of race, racism and discrimination always become the canter of the study of the African-American community, for example in literature. An example of African-American Literature that described those things is written by Phillis Wheatley. In her poems that were influenced by the Neoclassicism era, entitled: “On being brought from AFRICA to AMERICA'' and “To the Right Honourable William, Earl of Dartmouth”, she delivered the issues of race and racism. This paper aims to analyze racism toward African-America as described in Phillis Wheatley’s poems. The researcher employed a qualitative descriptive method in which the collected data were analyzed, interpreted, and described to answer the objective of the study. The primary data in this undergraduate thesis are two selected poems by Wheatley and the supporting data were taken from books, articles, journals, online sources, and other sources. The researcher applied African-American criticism to answer the objective of the research. The Researchers use three basic tenets of African-American criticism (Everyday Racism, The Social Construction of Race and Voice of color). The findings show Wheatley’s poems portray the life of an African American who experienced racism first-hand. The concept of racism in the two selected poems from Wheatley’s has correlation with 3 concepts of racism of African-American criticism, those are: Everyday racism, The Social Construction of Race, Voice of color.